Prototype Alat Keamanan Rumah Internet Of Things (Iot) Berbasis Nodemcu Esp8266 Dengan Esp32 Cam Dan Kombinasi Sensor Menggunakan Telegram - Danang Danang; Ekky Fredyan; Iman Saufik Suasana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Home security system is a term to describe a system of protection for residents in the environment and its surroundings from the interference of crime. A house has been equipped with high technology and can be connected to the security equipment in the house. Home security is made in order to create security, comfort and safety for residents of the house and can maintain the security of the environment without monitoring. Home security can be operated via a microcontroller and a mobile device. Home security in Indonesia is currently classified as very important, this is because the crime rate is increasing every year. The development of home security has been carried out using various existing technologies, such as the nodemcu microcontroller, which is a hardware platform intended to create prototypes of interactive electronic equipment based on flexible and easy-to-use hardware and software. This research was conducted to produce a simple home security system by utilizing nodemcu technology and a combination of sensors and an ESP32 cam as a medium to be able to run sensors and home security cameras. This research was conducted by conducting a literature study, exploring the technologies used, as well as the concept of mobile-based software development. The next step is to define requirements, analysis, design, and implementation (programming and testing the system that has been built).